The effect of fresh goat's milk on anthropometric overview in healthy women. - Yusni Yusni; Maryatun Maryatun (GarVal Editorial Ltda., 2021)
Context: Most people believe that goat milk contains high fat; therefore, regular consumption of goat milk will increase body weight. This assumption needs to be proven to be able to utilize the use of milk to improve public health. Aims: To analyze the effects of fresh goat milk on body weight and body mass index (BMI) in women. Methods: The research was an experiment study (pretest-posttest with control group design). A total of 18 volunteers, female, healthy, and aged 18-19 years have participated in the study. The subjects were divided into two groups: intervention group (treated with fresh goat milk) and control group (untreated with goat milk). Fresh goat milk is given in the morning between 08:00-09:00 a.m with a dose of 1× 250 mg/day and given for 110 days. Subjects for both groups were not given a special diet and without any dietary restrictions during the study as well as treatment. The subjects used had met the inclusion and exclusion criteria as subjects. Results: The results showed that there was a significant decrease of weight (before = 51.22 and after = 48.83; p = 0.001) and BMI (before = 21.18 and after = 20.02; p = 0.001) after goat milk consumption in the trial group. In the control group, there were no difference in weight (before = 53.72 and after = 53.05; p = 0.066) and BMI (before = 22.04 and after = 22.07; p = 0.068) before and after intervention of fresh goat milk. Conclusions: Regular consumption of fresh goat milk decreased weight and BMI; therefore, goat's milk can be useful for healthy nutrition for women; meanwhile, many factors that influence anthropometry were not analyzed in this study. Further research is needed for its use in reducing body weight in people with overweight/obesity.